Removable Partial Denture – Functional Impression Techniques: Review - de Moraes Melo Neto, Clóvis Lamartine [UNESP]; Turcio, Karina Helga [UNESP]; dos Santos, Daniela Micheline [UNESP]; Goiato, Marcelo Coelho [UNESP] (Charles University in Prague, Karolinum Press, 2023)
The objective of this article is to concisely review the main clinical techniques used to make the functional impression to manufacture a removable partial denture. Through this review, the dentist can develop his clinical knowledge.
Keywords: Clinical laboratory techniques; Dental impression technique; Dental prosthesis; Prosthodontic tooth preparation; Prosthodontics; Removable partial denture